posted by Tammy Evert on .
Solve each literal equations for the indicated variable
D = C - s/n ( for s)
s/n = D - C
Next, multiply both sides of the above equation by n, to get the equation for s.
i don't understand could you type it how it looks
This is an example Tammy
If you have z/b = x + y and you want the equation in z, then you multiply both sides by b, thus
b*(z/b)=b*(x + y) which gives you
z=b(x + y)
You could choose to leave it like this, unless distributing the b simplified the equation.
In your equation you're asked to multiply both sides by n.
THANK YOU SO MUCH
help... what is P - Q = -R, for Q
been out with the flu all week and don't have any examples like these? Thanks